Lack of evidence of rotavirus-dependent molecular mimicry as a trigger of coeliac disease. (29th September 2016) - Ziberna, F; De Lorenzo, G; Schiavon, V; Arnoldi, F; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Burrone, O R; Ventura, A; Not, T
Summary: New data suggest the involvement of rotavirus (RV) in triggering autoimmunity in coeliac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy-proven CD patients and 46 patients with potential CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. Using enzyme-linked immunosorbent assay (ELISA) assay, we measured immunoglobulin (Ig)A–IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476–487 aa) which shows a homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs) containing the VP7 protein and the double-layered RV-particles (DLPs) lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22 of 118 (18%) CD patients and in both paediatric (17 of 107, 16%) and adult (29 of 107, 27%) control groups, without showing a statistically significant difference among them ( P = 0·6, P = 0·1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34 of 118, 29% CD patients; 66 of 107, 62% adult controls) and control synthetic peptides (35 of 118, 30% CD patients; 56 of 107, 52% adult controls), suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. Graphical Abstract: